State capitalism, institutional adaptation, and the Chinese miracle - Naughton, Barry; Tsai, Kellee S. (New York, NY : Cambridge University Press, 2015)
China's stunning growth rates have corresponded with the rise of "state capitalism." Since the mid-2000s, China's political economy has stabilized around a model where most sectors are marketized and increasingly integrated with the global economy; yet strategic industries remain firmly in the grasp of an elite empire of state-owned enterprises. What are the implications of state capitalism for industrial competitiveness, corporate governance, government-business relations, and domestic welfare? How does China's model of state capitalism compare with other examples of state-directed development in late industrializing countries? As China enters a phase of more modest growth, it is especially timely to understand how its institutions have adapted to new challenges and party-state priorities. In this volume, leading scholars of China's economy, politics, history, and society explore these compelling issues.--
1. Introduction : state capitalism and the Chinese economic miracle / Kellee S. Tsai and Barry Naughton -- Section I: Evolution of the state sector. 2. State-owned business and party-state regulation in China's modern political economy / Margaret M. Pearson -- 3. The transformation of the state sector : SASAC, the market economy, and the new national champions / Barry Naughton -- Section II: Outcomes and processes. 4. Stability, asset management, and gradual change in China's reform economy / Dough Guthrie, Zhixing Xiao and Junmin Wang -- 5. The emergence and evolution of Chinese business groups : are pyramidal groups forming? / Dylan Sutherland and Lutao Ning -- 6. Competition and upgrading in Chinese industry / Loren Brandt and Eric Thun -- Section III: The big picture : historical, social, and systemic perspectives. 7. Explaining the dynamics of change : tranformation and evolution of China's public economy through war, revolution, and peace, 1928-2008 / Morris L. Bian -- 8. The evolution of a welfare state under China's state capitalism / Mark W. Frazier -- 9. Did China follow the East Asian development model? / Andrea Boltho and Maria Weber.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Capitalism -- China; China -- Economic policy -- 2000-; China -- Economic conditions -- 2000-; Chine -- Politique économique -- 2000-; Chine -- Conditions économiques -- 2000-; BUSINESS & ECONOMICS -- Economics -- General; BUSINESS & ECONOMICS -- Reference; Capitalism; Economic history; Economic policy; China; Politics and Government; Since 2000; Electronic books; Electronic books